Rodzina w epoce nowożytnej i jej miejsce w nauczaniu oraz podręcznikach historii (w kwestii wykorzystania tematów związanych z życiem codziennym) - Mihola, Jiří (Karkonoska Państwowa Szkoła Wyższa, 2011)
In compliance with the trends of modern historiography, matters of day-today life, mentalities and culture are gaining prominence during the creation of textbooks. The family of our ancestors as one of the places in which day-to-day life was played out is one of the attractive themes receiving deserved attention. The family is the subject not only of historical study, but also of sociological or culturalanthropological study. Research into the so-called demographic phenomena of birth, marriage and death occupies a significant position in the treatment of family history.
Keywords: history; everyday life; family; history book